INCREASED FLUID INTAKE IN PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS - Asmadiannor; Agustina, Rismia; Setiawati, Eka; Pangestika, Ghina; Hayatunnisa, Nor; Apriani, Rosina; Munawarah, Siti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Introduction: Some of the main nursing problems that arise in patients with chronic kidney failure undergoing hemodialysis are problems with excess fluid volume. The aim of this study was to describe increased fluid intake in patients with chronic kidney disease undergoing hemodialysis at Ulin General Hospital of Banjarmasin.Methods: This was a descriptive cross sectional study. 80 respondents were taken using consecutive sampling. The instruments used in this study were questionnaire of demographic, knowledge, attitude, family support, involvement of health workers and Inter-Dialytic Weight Gain (IDWG) calculation sheets.Results: The results showed that the majority of respondents were women (53.8%), the education of respondents was high school (28.8%), the average age of respondents was 48.19 years old, most respondents had been undergoing hemodialysis for less than 12 months (57.5%), the frequency of hemodialysis was 2 times each week (93.8%), the level of knowledge was good (42.5%) and moderate (42.5%), the family support was good (86.3%), the attitude was positive (55%), the involvement of health workers was good (60%), and the majority of respondents had moderate IDWG criteria (47.5%).Conclusion: Almost half of patients with chronic kidney disease who were undergoing hemodialysis at Ulin General Hospital of Banjarmasin had moderate IDWG which would render the treatment more complicated. Further study is needed to investigate related factors of excessive fluid intake in patients undergoing hemodialysis.